Efforts to Increase Teacher Motivation and Performance Through Supervision of Head Master SD Negeri 150 Seluma - Budi Harsono (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
Target of research of action go to school this is to improve performance and motivation learn SDN 150 Seluma pass activity of headmaster supervision. Its research type is research of school action. Activity of this research consist of step planning of action, execution of action, observation, and refleksi. Technique analyse data use technique of obeservasi. Instrumen observation the used is appliance assessment of ability of teacher in the form of instrument assessment of teacher performance and motivation . Result of research show finding that headmaster supervision of SDN 150 Seluma school year 2016 / 2017 can improve motivation work cycle of I equal to 29% becoming 86% mounting 57% and performance learn SDN 150 Seluma in cycle of I from 43% mounting to become 86% or there is make-up of equal to 43%Keywords: headmaster supervision, teacher motivation, teacher perform